KEPEMIMPINAN KOLABORATIF KEPALA SEKOLAH MENGHADAPI ERA SOCIETY 5.0 - Simanungkalit, Eva Marlina (STKIP Pesisir Selatan, 2025)
The Society 5.0 era brings significant changes in the world of education, demanding a comprehensive transformation of learning systems, teaching methods, and leadership models. This study focuses on the role of collaborative leadership by school principals as a key to facing the challenges and dynamics of education in this era. The literature study method was used to explore and analyze various literature related to the concept of collaborative leadership, digital transformation of education, and the development of student characteristics in the Society 5.0 era. This study aims to examine aspects of collaborative leadership styles to face the turbulent changes in the Society 5.0 era. In addition, it is hoped that this research can serve as a reference for school principals and leaders involved in the world of education to be ready and continue to survive and adapt to the changing times and the massive development of technology and information. The results of the study conclude that collaborative leadership that emphasizes cooperation and active participation among stakeholders in the school environment can create an inclusive, adaptive, and innovative learning culture. The principal acts as a facilitator who integrates various parties in decision-making and the implementation of educational programs synergistically, thereby strengthening the effectiveness of school management and preparing a competent generation ready to compete globally.